First Principles Study of Structural, Electronic and Magnetic Properties of Defected (Monovacant) Hexagonal Boron Nitride Sheet (Journal of Nepal Physical Society, 2021)
The structural, electronic, and magnetic properties of vacancy structures with triangular shape are related to the defect in single hexagonal boron nitride (h-BN) sheet. It is investigated by using density functional theory calculations. The first-principles calculations based GGA functionals have been implemented to study the structural, electronic and magnetic properties of pure and defected hexagonal boron nitride (h-BN) monolayer sheet using Quantum ESPRESSO (QE) package, 6.5 version. The calculated values of formation energy reveal the structural stability of the defected systems. The formation energies for B and N vacant system are found to be 16.45 eV and 12.87 eV respectively. This predicts that the N vacant system is more preferable with lower formation energy. The defect in h-BN seems to be changing its band gap and magnetic properties of h-BN system. The 6.25 % B-vacancy results h-BN to be half metallic ferromagnetic with total magnetization of 2.74µB/cell. Further, 6.25 % N-vacancy causes it to be magnetic semiconductor with total magnetization 1.00µB /cell.